2016
DOI: 10.1111/adb.12467
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level alcohol consumption during adolescence and its impact on cognitive control development

Abstract: Adolescence is a critical period for maturation of cognitive control and most adolescents start experimenting with alcohol around that time. On the one hand, recent studies indicate that low control abilities predict future problematic alcohol use. On the other hand, binge drinking during young adulthood can (further) impair cognitive control. However, so far no study examined the effects of low-level alcohol use during adolescence. In the present longitudinal fMRI study, we therefore investigated the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
(62 reference statements)
0
9
1
Order By: Relevance
“…The copyright holder for this preprint (which was this version posted November 7, 2017. ; https://doi.org/10.1101/215053 doi: bioRxiv preprint Individual reliability of fMRI 6 November 7, 2017 to examine the influence of substance consumption on brain development (for details see Jurk, Mennigen, Goschke, & Smolka, 2016;Ripke et al, 2012Ripke et al, , 2014Rodehacke et al, 2014;Vetter et al, 2015). Recently, we investigated the reliability of selected fMRI contrasts for the first two acquisition waves (Vetter et al, 2017).…”
Section: Longitudinal Data Case: Delay Discountingmentioning
confidence: 99%
“…The copyright holder for this preprint (which was this version posted November 7, 2017. ; https://doi.org/10.1101/215053 doi: bioRxiv preprint Individual reliability of fMRI 6 November 7, 2017 to examine the influence of substance consumption on brain development (for details see Jurk, Mennigen, Goschke, & Smolka, 2016;Ripke et al, 2012Ripke et al, , 2014Rodehacke et al, 2014;Vetter et al, 2015). Recently, we investigated the reliability of selected fMRI contrasts for the first two acquisition waves (Vetter et al, 2017).…”
Section: Longitudinal Data Case: Delay Discountingmentioning
confidence: 99%
“…A study using eight years of data from 2,226 youth in the Tracking Adolescents' Individual Lives Survey (TRAILS) found that light and heavy adolescent alcohol use was not associated with deterioration in executive functioning, compared to no alcohol use, when controlling for baseline performance, age, and tobacco use (55). A four-year study of 92 adolescents found low alcohol consumption was associated with subtle improvements in inhibitory control (56). No negative effect of low-level alcohol use on the development of school grades, spatial working memory or rapid visual processing was found.…”
Section: Neuropsychological Consequences Of Alcohol Usementioning
confidence: 99%
“…Some studies have also supported the inverse relationship and have proposed that the impairments observed in binge drinkers are the direct consequence of alcohol consumption. One study that targeted adolescent low drinkers indicated that alcohol consumption 4 years later (mean = 54 g per week at follow-up when participants were 18 years old) was not predicted by cognitive performance (inhibitory control and shifting) or brain activation (Jurk et al, 2016), suggesting that both cognitive impairments and brain modifications are the consequences of alcohol consumption rather than its cause.…”
Section: Questions and Perspectives For Future Researchmentioning
confidence: 99%